KUNCI KESUKSESAN REFORMASI BIROKRASI SINGAPURA: PEMBELAJARAN UNTUK PARA PEMBUAT KEBIJAKAN - Seno, Ramadhani Haryo (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2022)
Focus this research is to describe the process of public sector reform in a country, by finding the sectrets success in carrying out transformation and reform in Singapura. Descriptive qualitative analysis by study literature and examining secondary data as a data collection method use in this research. The results show that there are four secrets success of public sector reform in Singapore: (1) zero tolerance for corruption; (2) meritocracy in appointing and promoting someone in public sector or political office and making meritocracy the national identity and ideology. (3) Providing decent and competitive salaries to attract